PEMILIHAN KEPALA DESA ANTAR WAKTU DI DESA ANJANI KECAMATAN SURALAGA KABUPATEN LOMBOK TIMUR: INTERTIME THE ELECTION HEAD OF VILLAGE IN ANJANI VILLAGE, DISTRICT OF SURALAGA, EAST LOMBOK REGENCY - adnan, muhammad (Fakultas Hukum Universitas Gunung Rinjani, 2021)
The purpose of this study was to understand how the procedure of election head of village in Anjani Village District of Suralaga East Lombok Regency. And it also aims to understand what are the supporting factors and obstacles to the election head of village in Anjani Village District of Suralaga East Lombok Regency. This research examines the implementation of legal norms, in this case, legal norms about the intertime election (PAW) Village Head Election (Pilkades) with the selection of research locations conducted was purposively. This research is juridical-empirical, the data sources are library materials and the results of field interviews. The results of the research on the implementation of the inter-temporal Village Head Election in Anjani Village, Suralaga District, East Lombok Regency in 2021 carried out through an election mechanism with the village deliberation method led by the election committee based on the Minister of Home Affairs Regulation Number 65 of 2017 concerning Amendments to the Regulation of the Minister of Home Affairs Number 112 of 2014 about the Pilkades